INVESTIGATION OF THE FEASIBILITY OF CONSTRUCTING A MAP FOR COCONUT WITH SEVERAL F2 FAMILIES USING COMPUTER-SIMULATED DATA - C. K. Bandaranayake (International Coconut Community, 2003)
A computer simulation was performed using RiceSim computer software to explore the practicability of combining several different F2 populations together through JoinMap to mimic the real available coconut mapping populations, and found that it was very successful. JoinMap would be able to map all 16 chromosomes which covered the map length of 1540 cM except for a single marker on chromosome 8. The largest marker interval was 32 cM at the bottom of chromosome 3 and all other markers were evenly distributed along the chromosomes maintaining the space around 12-30 cM between them.